Goll et Witkacy : entre l’expressionnisme et le surréalisme - Kaczmarek, Tomasz (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
Studying works, especially theoretical texts of Yvan Goll and Stanisław Ignacy Witkiewicz it is difficult not to pay attention to many common points between these two great creators of the theatre. Supposing the Pole knew beyond a reasonable doubt surrealism and many other “isms” prevailing in Europe in the first decades of the twentieth century, it is quite sure that the Alsatian with Jewish origins did not have the opportunity to get acquainted with the achievements of the initiator of the Pure Form. Nevertheless, they both created the two similar, but slightly different from each other, theatrical aesthetics, which constitute a part of the Great Theatre Reform and they did it at the same time. Although these two strong artistic personalities did not know each other, they have developed an analogous innovative formula of expression, created in the crucible of multiculturalism, which at that time was the avant-garde Europe.